Mathematical functions of the rate of enzymatic reaction with Temperature, concentration of substrate and concentration of enzyme are proved that the divide differences are symmetrical in all their arguments - UDDIN, NIZAM (International Journal of Advanced Chemistry, 2013)
In this research paper, I used mathematical functions of the rate of enzymatic reaction for proving the divide differences are symmetrical in all their argument. The concentration of substrate is the limiting factor, as the substrate concentration increases, the Enzyme reaction rate increases. Assuming a sufficient concentration of substrate is available, increasing Enzyme concentration will increase the enzymatic reaction rate. The rise in Temperature accelerates an Enzyme reaction but at the same time causes inactivation of the protein. At certain Temperature known as the optimum Temperature the activity is maximum. Temperature, concentration of substrate and concentration of enzyme are increased the rate of enzymatic reaction at a limit which is called optimum limit. I take their values in mathematical form where “n” is optimum limit.